Emergency nurse practitioners and doctors consulting with patients in an emergency department: a comparison of communication skills and satisfaction. Issue 6 (22nd May 2009) - Sandhu, H; Dale, J; Stallard, N; Crouch, R; Glucksman, E
Abstract : Background: Emergency nurse practitioners (ENPs) play an increasingly important role in UK emergency departments (EDs), but there is limited evidence about how this affects patient care and outcome. A study was undertaken to compare the content of, and satisfaction with, consultations made with patients presenting with problems of low acuity to an ED. Methods: Patients presenting with "primary care" problems were allocated to senior house officers (SHOs, n = 10), specialist registrars/staff grades (n = 7), sessionally-employed general practitioners (GPs, n = 12) or ENPs (n = 6) randomly rostered to work in a consulting room that had a wall-mounted video camera. At the end of each consultation the doctor/ENP and the patient were asked to complete the Physician/Patient Satisfaction Questionnaire. A stratified sample of videotaped consultations (n = 296) was analysed in depth using the Roter Interaction Analysis System. The main outcome measures were length of consultation; numbers of utterances of doctor/ENP and patient talk related to building a relationship, data gathering, activating/partnering, and patient education/counselling; doctor/ENP and patient consultation satisfaction scores. Results: ENPs and GPs focused more on patient education and counselling about the medical condition or therapeutic regimen than did ED doctors. There were no significant differences in consultation length. ENPs had higher levels of overall self-satisfaction with their consultations than ED doctors. Patient satisfaction with how actively they participated in the consultation was significantly associated with the amount of talk relating to building a relationship and activating and partnering, and patient satisfaction with information giving in the consultation was significantly associated with the amount of talk relating to building a relationship. Conclusion: These findings suggest differences between ENP and ED doctor consultations which are associated with some aspects of patient satisfaction. In contrast to previous reports, consultation length was not greater for ENPs than for doctors. There is a need for further research to test the generalisability of these findings and their impact on clinical outcome.